2017
DOI: 10.1007/s40259-017-0223-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving Antibody-Based Cancer Therapeutics Through Glycan Engineering

Abstract: Antibody-based therapeutics has emerged as a major tool in cancer treatment. Guided by the superb specificity of the antibody variable domain, it allows the precise targeting of tumour markers. Recently, eliciting cellular effector functions, mediated by the Fc domain, has gained traction as a means by which to generate more potent antibody therapeutics. Extensive mutagenesis studies of the Fc protein backbone has enabled the generation of Fc variants that more optimally engage the Fcγ receptors known to media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 158 publications
0
51
0
Order By: Relevance
“…For example, margetuximab, developed by Mac-roGenics, had adapted the same Fab target (Her2) as transtuzumab but had been Fc-engineered to maximize immune effector function by elevating relative affinity to activating Fcγ receptor, FcγRIIIa over inhibitory Fcγ receptor, FcγRIIb, and it recently showed a 24% risk reduction in patients relative to that of trastuzumab in a phase 3 clinical trial in 536 breast cancer patients 69 . Other significant efforts have been directed to the engineering of antibodies with improved affinity for FcγRIIIa and enhanced effector function by amino acid mutations 36,[70][71][72][73][74] or glycan modifications [75][76][77][78][79][80][81] . Hatori and coworkers also engineered an antibody Fc variant (P238D/L328E) that showed selectively enhanced FcγRIIb binding over both FcγRIIa-R131 and FcγRIIa-H131 82 .…”
Section: Engineering Effector Functions Of Antibodiesmentioning
confidence: 99%
“…For example, margetuximab, developed by Mac-roGenics, had adapted the same Fab target (Her2) as transtuzumab but had been Fc-engineered to maximize immune effector function by elevating relative affinity to activating Fcγ receptor, FcγRIIIa over inhibitory Fcγ receptor, FcγRIIb, and it recently showed a 24% risk reduction in patients relative to that of trastuzumab in a phase 3 clinical trial in 536 breast cancer patients 69 . Other significant efforts have been directed to the engineering of antibodies with improved affinity for FcγRIIIa and enhanced effector function by amino acid mutations 36,[70][71][72][73][74] or glycan modifications [75][76][77][78][79][80][81] . Hatori and coworkers also engineered an antibody Fc variant (P238D/L328E) that showed selectively enhanced FcγRIIb binding over both FcγRIIa-R131 and FcγRIIa-H131 82 .…”
Section: Engineering Effector Functions Of Antibodiesmentioning
confidence: 99%
“…[40] Absence of core fucose leads to increased binding to FcyRIII, which increases the ADCC response in vitro [41] and increases activity in vivo, which leads to a lower required dose in the clinic. [42] Terminal Galactose Galactose depleted IgG exhibits a significantly reduced binding affinity to C1q [43][44][45] but increased binding to the mannosebinding lectin, which can also activate the complement pathway. [44] New findings by Subedi and Barb [41] showed that increased galactosylation leads to increased binding to FcγRIII Figure 2.…”
Section: N-glycosylationmentioning
confidence: 99%
“…Glycoengineering technology is becoming an attractive strategy to improve the pharmaceutical properties of therapeutic agents. There are many approaches for glycoengineering, including the introduction of new glycosylation sites to increase carbohydrate content or to block specific binding (Yu et al, 2017;Mimura et al, 2018). In this study, we generated 10 variants with six new consensus N-linked glycosylation sites within the HBS region.…”
Section: Discussionmentioning
confidence: 99%